Two histories one conflict: an analysis of the cyprus conflict within the framework of conflict resolution theory - Batu, Arda (My University, 2005)
Çok değişkenli ve karmaşık Kıbrıs sorunu bir den çok tarafı ilgilendirmekte ve kırk yılı aşkın süredir uluslararsı gündemi meşgul etmektedir. Bu çalışmada, Kıbrıs sorunundaki kritik gelişmelere genel bir bakışla özetlerken, özellikle 1950’li yıllardan bu yana süre gelen çözüm girişimlerinin üzerinde durulmuştur. Adadaki ihtilafa ilişkin unsurların incelenmesinde Avrupa Birliğinin rolü ve etkilerinin altı çizilmiştir. Süregelen çözüm girişimleri inceledikten sonra ihtilaf çözünürlüğü teorileri çerçevesinde Kıbrıs meselesi genel olarak analiz edilecektir; spesifik olarak bu meselenin neden bunca yıl, ve özellikle son on senede, çözülemediği araştırılacaktır. Özellikle son dönemde çözümsüzlükte pay sahibi faktörler işaret edilip çözüme giden yola ışık tutacak önerilerde bulunulmaya çalışılacaktır.

The multi-faceted and complex Cyprus conflict has significant implications for a number of parties and has been on the international agenda for over four decades. The following study involves an overview of the critical junctures of the Cyprus conflict, incorporating significant resolution-seeking efforts since the 1950s. We shall explore the issues associated with the conflict and the continuous efforts to unite the peoples of the island, with a special emphasis on the prospect of a united Cyprus joining the European Union. Upon assessing the conflict and numerous negotiation and mediation efforts, an analysis will follow, which will be structured around theories of conflict resolution so as to shed light on the reasons of the protracted nature of the conflict, to investigate where and how conflict resolution techniques have fallen short so-far, and finally to provide insight on appropriate and effective ways to resolve this case. In this chronological assessment, we shall show how the Cyprus conflict grew into a protracted and intractable conflict.
Keywords: Kıbrıs Sorunu; Kıbrıs_Uluslararası Statü; Kuzey Kıbrıs Türk Cumhuriyeti